G222(P) A Review of Skeletal Surveys 2008–2012 at KCH – A Safeguarding Perspective. (4th June 2013) - Moss, S; Soni, S; Akindolie, O
Abstract : Aims: We compared the skeletal surveys done at King's College Hospital (KCH) to the guidelines of the Royal College of Paediatrics and Child Health (RCPCH) and the Royal College of Radiologists (RCR). We reviewed the skeletal surveys performed in children for suspected Non-Accidental Injury (NAI). We included both radiological and social conditions for each patient. Methods: The KCH radiology department maintains a list of all skeletal surveys performed by it. We reviewed the cases of children aged between 0 and 16 yrs who had skeletal surveys between 2008 and 2012 using information held on the electronic patient record and PACS. Results: 100 skeletal surveys were performed on children aged between 0 and 16yrs between 2008 and 2012. 81 of these were for investigation of possible NAI, of which 37% proved positive for NAI. A more detailed look at these positive cases revealed that 81% of these were aged less than 1yr and 6% were greater than 2 years old. 88% of surveys completed all the recommended x-ray views but only 49% of children had a follow-up chest x-ray as recommended. 81% were carried out while the child was an inpatient. The majority of children were not previously known to social services, signified by the fact that only 19% were on a child protection plan. Since KCH is a tertiary referral centre many children came from outside of the Lambeth and Southwark boroughs (44%). Conclusions: KCH performs well against the standards set by the RCPCH and the RCR in performing skeletal surveys. The numbers stated above are comparable with other centres. KCH may see slightly higher numbers of children investigated for NAI, but this is due to the fact that it is a tertiary referral centre. The surrounding boroughs of Lambeth and Southwark are densely populated areas with a relatively young population compared to national averages. The population is multi-ethnic and diverse with high unemployment and poverty. These are all risk factors for NAI and the safeguarding team at KCH have to be especially alert to the possibility of NAI.